Power outage and project-based learning in an Argentine primary school: the key role of teachers - Fanaro, Maria de los Ángeles (Universidad Nacional del Litoral, 2021)
This paper deals with a Project Based Learning (PBL) experience in an Argentine primary school that was the result of a massive and extended power outage. Our immersion in the field involved non-participant observations in teachers’ meetings and in classes either inside or outside the classroom. We provide a description of the whole project development, identifying all hallmarks of PBL and reflecting on how it operates in the school dynamics. A conclusion is drawn on the outstanding role of teachers’ attitudes and actions as conditioning factors for PBL development, and thus, on teachers as key actors in class innovation. Keywords: PBL; pedagogical innovation; teacher; primary school